UJI DAYA HAMBAT EKSTRAK DAUN TAPAK KUDA (Ipomoea pes caprae (L) R. Br. ) TERHADAP Staphylococcus aureus - Alminsyah Alminsyah; Indria Hafizah; Sulastrianah Sulastrianah (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Ipomoea pes caprae (L) R. Br are commonly used by the Indonesian’s people to treat wounds, ulcers and as antioxidant.  Based  on  previous  research  it  was  contains  terpenoids,  saponins, alkaloids,  tannins  and flavonoids. The aim of this study is to determine inhibition capacity of I. pes caprae (L) R. Br leaf extract toward Staphylococcus aureus isolated from patients infected wounds at a concentration of 100 % , 50 % , 25 % , 12.5 %  ,  6.25  %  ,  3.125  %  and  1.56  %. This  research  was  conducted  with  post-test  design  with  a  control  only. Erythromycin is  used as a control. One gram of  extract dissolved  in  10  ml  of  chloroform. Inhibition  zone  is measured  by  paper  disc  diffusion  method  on  Mueller  Hinton agar. Bivariat  analysis  showed  that there  is statistically significant differences of diameters of inhibition zone from each concentration (p=0,00) including control (p=0,00). Conclusion of this study are I. pes caprae (L) R. Br leaf chloroform extract have capacity to inhibit S. aureus growth and the inhibition respond increase with concentration. Keywords : Ipomoea pes caprae (L) R. Br, Inhibition test, Erythromycin, Staphylococcus aureus